Performance analysis of the Spanish men's top and second professional football division teams during eight consecutive seasons - Errekagorri, I.; López del Campo, R.; Resta, R.; Castellano, J. (Sensors, 2023)
The present study aimed to analyse the performance of the Spanish men`s top (LaLiga1) and second (LaLiga2) professional football division teams for eight consecutive seasons (from 2011-2012 to 2018-2019). The variables recorded were Passes, Successful Passes, Crosses, Shots, Goals, Corners, Fouls, Width, Length, Height, distance from the goalkeeper to the nearest defender (GkDef) and total distance covered (TD). The main results were that (1) LaLiga1 teams showed lower values of Length from 2013-2014, and lower values of GkDef and TD from 2014-2015; (2) LaLiga2 teams showed fewer Passes and lower values of GkDef and TD from 2014-2015, and fewer Goals and lower values of Length from 2015-2016; and (3) LaLiga1 teams showed more Passes, Successful Passes, Shots and Goals and higher values of TD compared to LaLiga2 teams during the eight-season period. This study concludes that LaLiga1 teams showed fewer final offensive actions, LaLiga2 teams showed fewer Passes and Goals and the teams of both leagues played in a space with greater density (meters by player), covering less distance as the seasons passed. The information provided in this study makes it possible to have reference values that have characterised the performance of the teams.